A Igreja Universal do Reino de Deus, seu discurso religioso e seus projetos sociais: um estudo de avaliação à luz do conceito de diaconia - Borré, Melchisedec (2014)
This research sought to identify the effective relationship between the theory and practice of the neo-Pentecostal discourse regarding the diaconal work, specifically by the IURD. The following presents the general context of religion, its characteristics, types and main elements, highlighting the religious phenomenon and the issue of sacred in modern society. It describes the neo-Pentecostalism from its origin, its history, growth factors, the main theological aspects in Brazilian scenario and the Prosperity Theology; it analyses how it is developed the relation between faith and capitalism from IURD, it describes in religiousness perspective the diaconal work, its goals, dimensions and purposes, and identifies from bibliographic research, how the diakonia is really established in IURD social practice, highlighting its relationship with social, politics and cultural issues from Brazilian society. The bibliographic research is descriptive, bounded to the work of religious actions from IURD, and it was developed with the application of quantitative method, because it enables to obtain information related to the theme. Based on the results, we can conclude that the diaconal practice, in IURD perspective, presents certain conceptual ambiguity that, even having a significant amount of actions developed by different social projects, it doesn t effectively highlight a diaconal work, considered real and objective and that applies to the impoverished sectors of the society where there is insertion of the institution.